INTERACTION OF LASER RADIATION WITH MATTER : Simulation of spatial distribution of absorbed laser energy in spherical microcapsules. (28th September 2016) - Geints, Yu E; Zemlyanov, A A; Panina, E K
Abstract: Specific features of optical field distribution in composite spherical particles consisting of a liquid core and nanocomposite absorbing shell are theoretically studied at different wavelengths of incident radiation. Using the numerical simulation it is shown that the thickness of the shell of the spherical microcapsule particle and its intrinsic absorption coefficient determine the character of the spatial distribution and the absorbed power. The variation of these parameters allows one to change the spatial position of efficient volume absorption regions and peak absorption values. This provides favourable conditions for opening the shells in appropriate spatial zones to release the contents of the microcapsules.